3D printing performance using radio frequency electromagnetic wave modified potato starch. (August 2022) - Ma, Shu; Liu, Junbo; Zhang, Qianru; Lin, Qian; Liu, Rui; Xing, Yanan; Jiang, Hao
Abstract: In this study, the altered morphology, amylose content, microstructure, viscosity, and thermal properties of potato starch after being modified for different times (5, 10, 15, 20 and 30 mins) by radio frequency electromagnetic wave (RF) were studied. Obtained the most suitable RF modified time for 3D printing. The results showed that the RF treatment roughened the starch surface and reduced the amylose content, viscosity and pasting temperature of the starch. RF-treated starch gels displayed better print performance than untreated potato gels. Furthermore, RF-20 treatment offers better morphology indexes including clarity and the highest stack height, line uniformity and height retention of printed samples due to the fact that the RF treatment rearranges the internal structure of the potato starch granules, making the internal structure more stable and orderly. Overall, the RF treatment is an effective way to modify starch and optimize starch gels for 3D printing. Highlights: Radio frequency electromagnetic wave can modify the potato starch properties. Radio frequency electromagnetic wave reduced the amylose content of potato starch. Radio frequency electromagnetic wave reduced the peak viscosity of the starch. The starches were made into gels for 3D printing. Radio frequency electromagnetic wave treated for 20 min starch was suited for 3D printing.